Development Economics 2014
DOI: 10.1057/9781137555229_13
|View full text |Cite
|
Sign up to set email alerts
|

The Informal Labour Market in India: Transitory or Permanent Employment for Migrants?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…15-24 years, 25-34 years, 35-60 years, and above 60 years (reference category) have been considered. Rural male out-migration is affected by the caste system prevalent in India (Panda 1986;Haberfeld et al 1999;Singh 1997;Mosse et al 2005;Junankar and Shonchoy 2013). Hence the population has been categorised into three classes, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15-24 years, 25-34 years, 35-60 years, and above 60 years (reference category) have been considered. Rural male out-migration is affected by the caste system prevalent in India (Panda 1986;Haberfeld et al 1999;Singh 1997;Mosse et al 2005;Junankar and Shonchoy 2013). Hence the population has been categorised into three classes, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the younger males aged 15-24 years are relatively less likely to migrate as they are five times more likely to migrate than the males aged more than 60 years. Caste status appears to be another important correlate of rural male out-migration (Singh 1997;Mosse et al 2005;Junankar and Shonchoy 2013). The privileged caste group which is least likely to migrate is the reference category.…”
Section: Probability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Shonchoy and Junankar (2013) observed that those household heads that were belonging from lower social groups (castes and religions) were more likely to be found in the informal sector of India. The importance of caste in entrepreneurship has been closely examined by Iyer et al (2013), where it is found that Scheduled Castes (SCs) and Scheduled Tribes (STs) are underrepresented in ownership of enterprises in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the informal economy in India employs over 80 per cent of non‐agricultural workers (Rothboeck and Kring, 2014). Broadly the informal labour market comprises of workers in the informal sector plus casual workers employed in the formal sector (Shonchoy and Junankar, 2014). In India, the dichotomy between formal and informal is not distinctive and policy makers tend to factor in both.…”
Section: The Indian Contextmentioning
confidence: 99%